Boundaries of the Educational Imagination - Hugo, Wayne, 1964- (Book collections on Project MUSE., 2016)
The educational imagination is the capacity to think critically beyond our located, daily experiences of education. It breaks away from the immediacy of personal understanding by placing education within wider, deeper and longer contexts. Boundaries of the Educational Imagination develops the educational imagination by answering six questions: What happens when we expand continuously outwards from one school to all the schools of the world?; What happens if we go inside a school and explore how its material equipment has changed over the past 300 years?; What is the smallest educational unit in our brain and how does it allow an almost infinite expansion of knowledge?; What is the highest level of individual development we can teach students to aspire towards?; What role does education play in a world that is producing more and more complex knowledge increasingly quickly?; How do small knowledge elements combine to produce increasingly complex knowledge forms? Each question goes on a journey towards limit points in education so that educational processes can be placed within a bigger framework that allows new possibilities, fresh options and more critical engagement. These questions are then pulled together into a structuring framework enabling the reader to grasp how this complex subject works.